2006
DOI: 10.1007/s10592-006-9212-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of an endangered capercaillie (Tetrao urogallus) population at the Southern edge of the species range

Abstract: The low-latitude limits of species ranges are thought to be particularly important as long-term stores of genetic diversity and hot spots for speciation. The Iberian Peninsula, one of the main glacial refugia in Europe, houses the southern distribution limits of a number of boreal species. The capercaillie is one such species with a range extending northwards to cover most of Europe from Iberia to Scandinavia and East to Siberia. The Cantabrian Range, in North Spain, constitutes the contemporary south-western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 53 publications
(51 reference statements)
7
72
1
7
Order By: Relevance
“…Cantabrian capercaillie occupies a very southerly range within the grouse family (Quevedo et al 2006b), and has recently been identified as an Evolutionarily Significant Unit because of its unique ecological and genetic characteristics (Rodríguez-Muñoz et al 2007). The population appears to show low recruitment, with values as low as 0.54 juveniles per hen at the end of the summer and 74% of broodless hens in an 8-year period (Bañuelos et al this study, see ''Methods'' for details).…”
Section: Introductionmentioning
confidence: 97%
“…Cantabrian capercaillie occupies a very southerly range within the grouse family (Quevedo et al 2006b), and has recently been identified as an Evolutionarily Significant Unit because of its unique ecological and genetic characteristics (Rodríguez-Muñoz et al 2007). The population appears to show low recruitment, with values as low as 0.54 juveniles per hen at the end of the summer and 74% of broodless hens in an 8-year period (Bañuelos et al this study, see ''Methods'' for details).…”
Section: Introductionmentioning
confidence: 97%
“…Hence, the population may be expected to show marked ecological and behavioral differentiation related to its distinct habitat. Although the population is known to be an evolutionary significant unit and may be part of a distinct southern capercaillie lineage (Duriez et al 2007; Rodríguez-Muñoz et al 2007), its potential ecological peculiarities remain largely unknown (e.g. Storch 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogenetic studies indicate that the subspecies T. u. cantabricus (Castroviejo 1967(Castroviejo , 1975, an endemic of the Cantabrian Mountains of northwest Spain, forms a clade different from other European capercaillie (Rodríguez Muñ oz et al 2006), qualifies to be considered as an Evolutionarily Significant Unit (Moritz 1994(Moritz , 2002, and therefore deserves international conservation concern.…”
Section: Introductionmentioning
confidence: 99%